Hepatic Nuclear Receptor Expression Associates with Features of Histology in Pediatric Nonalcoholic Fatty Liver Disease. Issue 10 (27th September 2018) - Elbel, Erin E.; Lavine, Joel E.; Downes, Michael; Van Natta, Mark; Yu, Ruth; Schwimmer, Jeffrey B.; Behling, Cynthia; Brunt, Elizabeth M.; Tonascia, James; Evans, Ronald
Abstract : Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in children and adults. This study examined the relationship between hepatic nuclear receptor (NR) expression and histologic features of NAFLD. Drugs targeting a variety of NRs for nonalcoholic steatohepatitis (NASH) are in clinical trials. Liver messenger RNA was isolated from 40 children (10‐19 years) undergoing end‐of‐treatment biopsy in the Treatment of NAFLD in Children (TONIC) trial. High‐throughput quantitative polymerase chain reaction assayed NR messenger RNA. Cluster analysis was used to group 36 NRs, and NR levels were related to histologic measures of specific NAFLD features. Cluster analysis determined five groupings of NRs. Significant ( P < 0.05) differential expressions of specific NRs associated with histologic measures include farnesoid X receptor alpha and retinoic acid receptor (RARβ and RARβ) for steatosis; estrogen receptor alpha (ERα) and peroxisome proliferator‐activated receptor gamma 3 (PPARγ3) for hepatocellular ballooning; ER and PPARγ2 for lobular inflammation; PPARα/δ/γ1/γ2, ERα, constitutive androstane receptor, chicken ovalbumin upstream promoter transcription factor 1, RARα, RARβ1, retinoid X receptor, pregnane X receptor, thyroid hormone receptors α and β, and nuclear receptor related‐1 for fibrosis; and ERα and RARβ/β1/α for diagnosis of NASH. Conclusion : Differential expression of specific NRs correlates with histologic severity of specific NAFLD features. These NRs are pleiotropic transactivators regulating basal metabolic functions and inflammatory responses. Derangement of activity of these receptors in NAFLD provides a rationale for exploiting their ability with receptor‐specific ligands to ameliorate NASH and its consequences. Abstract : Expression of 36 nuclear receptors (NR) was quantified in end‐of‐treatment liver biopsies from the Treatment of NAFLD in Children (TONIC) trial. Differential expression of specific NRs correlates with histologic severity of NAFLD features in this pediatric cohort.